Composition and Properties of Lightweight Concrete of Variotropic Structure Based on Combined Aggregate and Microsilica - Evgenii M. Shcherban’; Sergey A. Stel’makh; Levon R. Mailyan; Alexey N. Beskopylny; Alexander L. Mailyan; Natalya Shcherban’; Andrei Chernil’nik; Diana Elshaeva (Buildings, 2025)
The use of artificial porous aggregates for the production of lightweight cement concrete is widespread and used everywhere. In most cases, lightweight artificial aggregates are used to produce concrete of the standard structure using vibration technology. However, there is currently no knowledge base on the use of these aggregates for the production of concrete using centrifugation technology. The purpose of this work is to develop and obtain a new composition of variotropic concrete with a combined coarse aggregate and microsilica. A total of 17 concrete elements of the annular cross-section were manufactured using centrifugation technology. The optimal ratio of 60% crushed stone (CrS) and 40% expanded clay gravel (EC) was determined. It was found that replacing CrS with EC improves such properties as density and thermal conductivity, and negatively affects the strength of the composite. Modification of lightweight centrifuged concrete on a combined aggregate with microsilica (MS) in dosages from 2% to 10% had a positive effect on its mechanical properties. The most effective MS dosage was 6%. The compressive strength of lightweight concrete increased by 14.75%, from 36.6 MPa to 42.0 MPa, which is comparable to the compressive strength of centrifuged concrete on a heavy aggregate of 43.4 MPa. The density value was 2148 kg/m3. The thermal conductivity coefficient was 1.270 W/m×°C. As a result, a new centrifuged concrete of variotropic structure with reduced material consumption, density, thermal conductivity coefficient, and the required mechanical properties was developed.